S.JUMAǴULOV PROZASÍNDA YUMORLÍQ OBRAZDÍŃ BIRINShI BETTE JARATÍLÍWÍ - Kudiyarova, R. (SCIENCE and SOCIETY, 2025)
In this article, we would like to focus on the first-person narrative of humorous characters in S. Jumagulov’s prose works. In this regard, the protagonist’s monologues and dialogues are of great importance. We witnessed the author’s use of the first-person narrative in creating the image of the hero, using a unique method to create a humorous image. In this article, we specifically addressed this issue and talked about the writer’s ability to create images.